A avaliação ambiental estratégica no contexto brasileiro: efetividade e desafios jurídico-institucionais - Bastos, Marina Montes (2015)
This work aims to study the instrument called Strategic Environmental Assessment (SEA) applied in the Brazilian context, to discover (1) if SEA in Brazil can be effective in the sense of actually influencing decision-making and change the environmental culture regarding the environment; (2) which factors can influence this effectiveness; and (3) in which way the legal-institutional dimension can influence effectiveness in Brazil. To do so, this work will first make a literature overview about SEA and effectiveness, adopting the premise that effectiveness, for the proposals of this work, is equal to ―real influence of SEA in decision-making processes and change of governmental view regarding the environment‖ – which may consequently promote sustainable development. This first part will also describe the main advantages, challenges and good practices of SEA presented by literature, and briefly describe SEA institutionalization in Brazil and the Netherlands (as an example of a successful case). In the second part, it will present a case study of the SEA made for Hydroelectric Generation Program of Minas Gerais (PGHMG), to verify its effectiveness and which factors have interfered in it. The third topic will then extract lessons learned from the PGHMG case, especially concerning the legal-institutional dimension of SEA, and how it can influence SEA effectiveness. The question to be answered, in the third part of this work, is whether an open rule that gives plenty of opportunity for the government to decide if, when and how to implement SEA (as in the PGHMG case) is the ideal rule in the Brazilian context. Our hypothesis is that SEA has the potential to be used effectively in the decision making process of the Brazilian government and to alter the governmental view regarding the environment, having the power to promote sustainable development, despite having to overcome considerable obstacles related to policy and institutional issues; to be implemented in a national scale, still according to our hypothesis, it is necessary to develop more restrictive rules regarding administrative discretion, in order to create an obligatory SEA procedure by the government.